2020
DOI: 10.1111/1751-7915.13596
|View full text |Cite
|
Sign up to set email alerts
|

Safety of photosynthetic Synechococcus elongatus for in vivo cyanobacteria–mammalian symbiotic therapeutics

Abstract: The cyanobacterium Synechococcus elongatus (SE) has been shown to rescue ischaemic heart muscle after myocardial infarction by photosynthetic oxygen production. Here, we investigated SE toxicity and hypothesized that systemic SE exposure does not elicit a significant immune response in rats. Wistar rats intravenously received SE (n = 12), sterile saline (n = 12) or E. coli lipopolysaccharide (LPS, n = 4), and a subset (8 SE, 8 saline) received a repeat injection 4 weeks later. At baseline, 4 h, 24 h, 48 h, 8 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…However, it would be far more interesting to search for immunotolerant photosynthetic microorganisms capable of establishing long-term relationships with humans. As discussed previously in this work, this idea is supported by evidence which indicates that vertebrate immune responses to photosynthetic organisms, even after systemic injection ( Williams et al, 2020 ), are mild or non-existent. It is conceivable that the mammalian immune response might have evolved in the absence of the need to recognize photosynthetic cells as foreign entities ( Wheeler et al, 2008 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, it would be far more interesting to search for immunotolerant photosynthetic microorganisms capable of establishing long-term relationships with humans. As discussed previously in this work, this idea is supported by evidence which indicates that vertebrate immune responses to photosynthetic organisms, even after systemic injection ( Williams et al, 2020 ), are mild or non-existent. It is conceivable that the mammalian immune response might have evolved in the absence of the need to recognize photosynthetic cells as foreign entities ( Wheeler et al, 2008 ).…”
Section: Discussionsupporting
confidence: 77%
“…By inducing photosynthetic activity through the exposure of S. elongatus to light, they were able to rescue the myocardium from acute ischemia, and showed that this effect was associated with an increase in tissue oxygenation, and improved cellular metabolism, ventricular function and performance, relative to rats treated by injection of non-illuminated S. elongatus and saline controls ( Cohen et al, 2017 ). Importantly, S. elongatus was found to be non-toxic and non-pathogenic in recipient rats, while in a follow-up study, S. elongatus failed to evoke an immune response when injected intravenously into Wistar rats, making this an intriguing and potentially feasible approach for the treatment of myocardial ischemia ( Williams et al, 2020 ).…”
Section: Photosynthetic Approaches For Tissue Oxygenationmentioning
confidence: 99%
“…Our group has previously demonstrated the safety of S. elongatus- based therapy when administered systemically 12 , 37 . Across all metrics, animals that received S. elongatus responded comparably to control animals, displaying no clinically significant immune response.…”
Section: Discussionmentioning
confidence: 99%
“…This natural human-microbial consortium suggests the possibility of generating viable endosymbiotic chimeric tissues, and of using photosynthetic microorganisms to build a symbiotic system to facilitate the survival of mammalian cells for transplantation and to improve therapies for particular diseases. Recently, Williams KM et al confirmed the safety of Synechococcus elongatus for development of cyanobacteria-mammalian symbiotic therapeutics through detecting the various immunological indicators in rats [103]. Another two studies, which generated a viable plant-vertebrate chimera [104] and synthetic chloroplast, respectively, demonstrated the possibility of creating a symbiotic system involving mammalian cells and algae [105].…”
Section: Summary and Perspectivementioning
confidence: 99%